Efek Anestesi Inhalasi Sevofluran dan Isofluran Terhadap Frekuensi Nadi - Fatimah, Aulia Nurul; Sudjito, Mulyo Hadi; Probandari, Ari (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: Anesthesia is an important part of the surgery. Sevoflurane and isoflurane are two inhalation anesthesia drugs have been commonly used. During anesthesia, one of indicators should be monitored is frequency of pulse. This research aimed to know the effects of these two drugs to the frequency of pulse. Methods: This research was an analytical observational research with the approach of cross sectional. The sample was taken by consecutive sampling after being selected based on the inclusion and exclusion criteria. Totally, 50 patients were divided into two groups of inhalation anesthetic sevoflurane and inhalation anesthetic sevoflurane and isoflurane. Data was analyzed with independent t test. Results: The p values on t-independent test in the early phase of the pulse frequency, phase induction and phase intubation were 0.04; 0.00; 0.02, and of the phase 5â of incision, 10âof incision and 15âof incision were 0.02; 0,0; 0.03. This results showed statistical significant of mean of pulse-frequency difference between sevoflurane and isoflurane in each of phase of inhalation anesthesia. Conclusions: Both sevoflurane and isoflurane influence the frequency of pulse. The mean of pulse frequency by isoflurane is higher than sevoflurane. However, inhalation anesthesia sevoflurane provides better stability than isoflurane. Keywords: Anesthetic Inhalation, Frequency of Pulse, Isoflurane, Sevoflurane